2011
DOI: 10.1080/14786411003774320
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allergic effect of the flavonoid myricitrin fromMyrica rubraleaf extractsin vitroandin vivo

Abstract: Flavonoids are ingested by the general population as anti-oxidant and anti-inflammatory agents. In this study, we investigated the effects of myricitrin, a flavonoid rich in Myrica rubra leaf, upon anti-inflammatory action. Myrica rubra leaf extracts inhibited pro-inflammatory TNFα production in a macrophage cell line, Raw264.7 cells. We observed that the serum IgE levels in the leaf extract-treated DO11.10, a mouse allergy model, were down-regulated. HPLC was performed to demonstrate that M. rubra leaf extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 15 publications
1
33
0
2
Order By: Relevance
“…Myricetin showed significant antinociceptive effect in the acetic acid-induced writhing test and in the second phase of formalin method, and this reduction has already been associated to the PGE2 reduction in peritoneal fluid (Tong et al, 2009). In previous studies myricitrin, myricetin and quercetin were able to reduce NO and TNF-a production in cellular models of inflammation (Park et al 2008;Shimosaki et al, 2011). In the present study, AE, myricitrin and myricetin exhibited potent inhibitory activity on NO and TNF-a production, and stimulatory activity on IL-10 production.…”
Section: Discussionmentioning
confidence: 95%
“…Myricetin showed significant antinociceptive effect in the acetic acid-induced writhing test and in the second phase of formalin method, and this reduction has already been associated to the PGE2 reduction in peritoneal fluid (Tong et al, 2009). In previous studies myricitrin, myricetin and quercetin were able to reduce NO and TNF-a production in cellular models of inflammation (Park et al 2008;Shimosaki et al, 2011). In the present study, AE, myricitrin and myricetin exhibited potent inhibitory activity on NO and TNF-a production, and stimulatory activity on IL-10 production.…”
Section: Discussionmentioning
confidence: 95%
“…In first case, a leaf extract rich in the flavonol myricitrin decreased total IgE in an allergy model in transgenic mice [29]. The flavones chrysin and apigenin suppressed total IgE concentrations whereas IgG, IgM and IgA concentrations were not affected [30] but later studies show that apigenin in a mice model of atopic dermatitis decreased serum total IgG1 and IgE concentrations, without modifying significantly specific antibodies, and ameliorated the development of skin lesions [12].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, myricitrin has been reported as a nitric oxide ( Å NO) and protein kinase C inhibitor that exerts antinociceptive effect [15]. The anti-inflammatory potential of myricitrin was demonstrated by Shimosaki et al [16] who found inhibitory effect of myricitrin against TNF-a production in RAW264.7 macrophages. Myeloperoxidase activity, closely related to the progression of chronic inflammatory diseases as well as neurodegenerative and coronary disorders, was irreversibly inactivated by myricitrin [17].…”
Section: Introductionmentioning
confidence: 96%